Genetic analysis of yield attributing traits in F2 generation of greengram [Vigna radiata (L.) Wilczek] - T. Nivethitha1 , C. Babu2 *, P. Jayamani1 , N. Senthil3 and K. Bhuvaneswari4 (Electronic Journal of Plant Breeding, 2023)
Extensive knowledge on the variability parameters and frequency distribution of desirable traits could assist the plant breeders in formulating selection criteria for enhancing the genetic gain under selection. The F2 populations of two greengram crosses viz., COGG13-39 x VGG16-058 and COGG13-39 x VGG18-002 were evaluated for nine biometrical traits during rabi, 2022. Magnitude of difference between PCV and GCV estimates was less than 2.50% for traits viz., pods/plant, pod length, seeds/pod and hundred seed weight in both the populations. High heritability and GAM coupled with moderate to high GCV observed for pods/cluster, pods/plant, hundred seed weight and seed yield/plant signifies the role of additive gene action. Frequency distribution results pointed out that these traits were positively skewed in both the populations. Therefore, stringent selection of segregants with desirable traits and utilizing them in yield improvement programme in greengram can be effectuated.